2017
DOI: 10.1111/cbdd.13073
|View full text |Cite
|
Sign up to set email alerts
|

Novel menadione hybrids: Synthesis, anticancer activity, and cell‐based studies

Abstract: A series of novel menadione-based triazole hybrids were designed and synthesized by employing copper-catalyzed azide-alkyne cycloaddition (CuAAC). All the synthesized hybrids were characterized by their spectral data ( 1 H NMR, 13 C NMR, IR, and HRMS). The synthesized compounds were evaluated for their anticancer activity against five selected cancer cell lines including lung (A549), prostate (DU-145), cervical (Hela), breast (MCF-7), and mouse melanoma (B-16) using MTT assay. The screening results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The considerable interest in these compounds is based on their pharmacological activities, especially as antimicrobial [ [8] , [9] , [10] , [11] ] and antitumor agents [ [12] , [13] , [14] , [15] ]. Most recently, 1,4-naphthoquinones, such as menadione (vitamin K3), have aroused a lot of interest due to relevant anticancer activity [ 16 ]. With specific attention on the anti-tubercular activity, studies have reported on the potential of using naphthoquinones as active agents against drug-resistant M. tuberculosis strains, although their mechanism of action has yet to be unveiled [ [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%
“…The considerable interest in these compounds is based on their pharmacological activities, especially as antimicrobial [ [8] , [9] , [10] , [11] ] and antitumor agents [ [12] , [13] , [14] , [15] ]. Most recently, 1,4-naphthoquinones, such as menadione (vitamin K3), have aroused a lot of interest due to relevant anticancer activity [ 16 ]. With specific attention on the anti-tubercular activity, studies have reported on the potential of using naphthoquinones as active agents against drug-resistant M. tuberculosis strains, although their mechanism of action has yet to be unveiled [ [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%
“…To validate whether barbatic acid ( 21 ) indeed caused apoptosis in A549 cells, we analyzed the nuclear fragmentation in treated cells, as one of the characteristics of apoptosis includes chromatin condensation and fragmentation of nuclei in inducing programmed cell death [32]. To achieve this, we treated A549 cells with 1 and 2 µM concentrations of barbatic acid for 48 h. Microscopic examination of Hoechst stained cells revealed chromatin condensation and fragmented nuclei indicating induction of apoptosis in A549 cells due to compound treatment (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…After fixation cells were incubated with RNase A (0.1 mg/mL) at 37 °C for 30 min and stained with propidium iodide (Sigma Aldrich, St. Louis, MO, USA) (50 μg/mL) for 30 min on ice in dark. Cell cycle analysis was performed by flow cytometry (Becton Dickinson FACS Caliber instrument) [32].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with clofazimine, it appears that menadione, which is also known as vitamin K3, has attracted more attention from the perspective of cancer treatment. Menadione has been identified to exhibit significant therapeutic benefits in the treatment of gastric cancer ( 55 ), prostate cancer ( 56 ), oral cancer ( 57 ) and breast cancer ( 58 ). Furthermore, the latest research indicated that menadione may increase anticancer activity by combining ROS-generating agents ( 59 ), but how it works in ESCA treatment requires further investigation.…”
Section: Discussionmentioning
confidence: 99%